Apollo The Definitive Sourcebook - Orloff, Richard W.; Harland, David M. (Space Exploration, 2006)
On 25 May 1961, John F Kennedy announced the goal of landing an American man on the Moon by the end of the decade. This challenge forced NASA to review the planned lunar landing of a three-man spaceship named Apollo in the mid-1970s. In 1962, it was decided that a specialized vehicle would accompany the main spacecraft, to make the lunar landing while the mothership remained in lunar orbit. To send these vehicles to the Moon would require the development of an enormous rocket. Development was protracted, but in December 1968 Apollo 8 was launched on a pioneering mission to perform an initial reconnaissance in lunar orbit. When Apollo 17 lifted off from the Moon in December 1972, the program was concluded. Now, at long last, there is a real prospect of a resumption of human exploration of the Moon. This book provides an overview of the origins of the Apollo program and descriptions of the ground facilities, launch vehicles and spacecraft that will serve as an invaluable single-volume sourcebook for space enthusiasts, space historians, journalists, and programme-makers on radio and TV. It supplements tha other books that have focused on the politics and management of the Apollo program, the astronauts, and their training and exploits.